KELAYAKAN USAHA BUDIDAYA ULAT SUTERA (BOMBIX MORI L.) BERDASARKAN ASPEK NON FINANSIAL KABUPATEN BOALEMO - Murni Djabar; Nurnaningsih Utiarahman (Universitas Andi Djemma Palopo, 2019)
The purpose of this study was to determine the feasibility of the business based on non-financial aspects of silkworm cultivation. The results of this study were with high demand and with a guarantee of the cocoon market, silkworm cultivation business conducted in the Tangga Barito village, the working area of of KPHP Unit V Boalemo worthy of doing. Cocoon selling prices of Rp. 40,000 is a standard price that is appropriate for quality b (medium) cocoons. To increase the added value of mulberry cultivation, it can endeavor to manufacture mulberry tea which is used as an antioxidant drink or to process silkworm waste into organic fertilizer. For technical and technology aspects starting from the business location, the location of caterpillar maintenance in general is close to the residence so as to facilitate maintenance and supervision. Silkworm cultivation is prepared starting from the building of silkworms to how to control pests and diseases that attack silkworms. The organization in question consists of informing matters relating to the cultivation of silkworms, directing, coordinating the development of mulberry and silkworm maintenance demonstration plots. From these results the silkworm business is feasible to run.Keywords: Aspect of non financial, Boalemo, Business feasibility, silkworms